Meningkatkan Kemampuan Kepala Sekolah dalam Menyusun Visi Sekolah Melalui Bimbingan Intensif Pada SMP Negeri 10 Sungai Kakap - Lili Ng Chui Mi (Jurnal Visi Ilmu Pendidikan, 2015)
This study departs from the principal background in formulating the school's vision not incorporate elements of skill, because there is a deep understanding of the formulation of the school's vision. this can be known when researcher holds managerial supervision by looking at the KTSP documents​​ made, where in chapter II contains the vision of the school. This study aims to improve the ability of principals in formulating the school's vision. The research method used is a form of qualitative descriptive approach. Datas were collected through interviews, observation, and discussion. The implementation procedure consisted of stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. The results showed that through intensive counseling can improve the ability of principals in formulating the school's vision, this can be evidenced from the observation from cycle 1 to cycle 2. Before the guidance, the school's vision reads: "faithful and devoted, Achievement and Noble". After the guidance, the vision formulation showed an increase with the addition of skilled phrase is "faithful and devoted, Achievement, Skilled and noble." Kata Kunci:   Kepala Sekolah, Visi Sekolah dan  Bimbingan Intensif